PENGARUH LOCUS OF CONTROL, KOMITMEN PROFESIONAL, PENGALAMAN AUDIT TERHADAP PERILAKU AKUNTAN PUBLIK DALAM KONFLIK AUDIT DENGAN KESADARAN ETIS SEBAGAI VARIABEL PEMODERASI - Utami, Intiyas; Noegroho, Yefta Andi Kus; Indrawati, Fenny (UI Scholars Hub, 2007)
Phenomena in public accountant that client pressure exists in an audit conflict situation are prevalent in the audit environment. Theoretical linkages between personality, ethical reasoning and ethical behavior were interesting to study. This paper studies those phenomena with behavioral research in accounting. This paper investigates the interaction effects o f locus o f control, professional commitment, audit experience and ethical reasoning on the behavior o f public accountants in the audit conflict situation. The data were collected through mail survey from fifty-two public accountants from CPA firm in DK1 Jakarta, Semarang, and Surabaya. The convenience sampling method was used in this research, because the population o f public accountants ’ that worked in CPA firm was unknown. The analyses technique was multiple regressions. The results o f this research showed that the variables locus o f control, professional commitment and ethical reasoning provides a better explanation for audit practice in a public accountants' ethical decision-making. Other results o f this research show that audit experience have not interaction effect to explain audit practice in a public accountants’ ethical decision-making.